Furfural: a renewable and versatile platform molecule for the synthesis of chemicals and fuels. Issue 4 (1st February 2016) - Mariscal, R.; Maireles-Torres, P.; Ojeda, M.; Sádaba, I.; López Granados, M.
Abstract : The aim of this review is to discuss the most relevant chemical routes for converting furfural to chemicals and to biofuels and additives. Abstract : The production of future transportation fuels and chemicals requires the deployment of new catalytic processes that transform biomass into valuable products under competitive conditions. Furfural has been identified as one of the most promising chemical platforms directly derived from biomass. With an annual production close to 300 kTon, furfural is currently a commodity chemical, and the technology for its production is largely established. The aim of this review is to discuss the most relevant chemical routes for converting furfural to chemicals, biofuels, and additives. This review focuses not only on industrially produced chemicals derived from furfural, but also on other not yet commercialised products that have a high potential for commercialisation as commodities. Other chemicals that are currently produced from oil but can also be derived from furfural are also reviewed. The chemical and engineering aspects such as the reaction conditions and mechanisms, as well as the main achievements and the challenges still to come in the pursuit of advancing the furfural-based industry, are highlighted.